Competition or conflict? Beyond traditional ordo-liberalism - Malte Dold; Tim Krieger (Albert-Ludwigs-Universität Freiburg, Wilfried-Guth-Stiftungsprofessur für Ordnungs- und Wettbewerbspolitik, 2017)
According to the traditional ordo-liberal view of the Freiburg School, the central role of the state in economic affairs is to set up rules that create a competitive order within which private actors have sufficient incentives to coordinate their economic affairs efficiently. Underlying this view is the implicit assumption that, given the right institutional framework, competition within markets is mainly characterized by peaceful and conflict-free rivalry between actors that leads to an optimal allocation of resources. In such a setting, competition may be described as a "record-type" game. This view, however, ignores the possibility that competition itself may very well trigger conflict rather than having an appeasing effect. In this case, competition appears to be a "struggle-type" game in which competitors invest in conflict activities that are not efficiency enhancing but rather resource wasting. Against this background, ordo-liberalism has yet to provide a clear-cut distinction between competition and conflict. In addition, it fails to identify - in a normative way - which institutional and regulatory framework could hamper conflict sensitivity of economic competition, given the harmful effect of conflict on the security of property rights. Our contribution investigates how the ordo-liberal research program needs to be extended when introducing conflict.
Keywords: B25; D02; D4; D63; D74; 330; ordo-liberalism; Freiburg School; conflict economics; competition